Using Leg Fins and Swimming Gloves and Their Effect on Developing 50m Butterfly Achievement - Salahaddin, Mustafa (Journal of Physical Education, 2010)
The problem of the research lied in the lack of leg swimming fins and swimming glove use for developing butterfly achievement. The aim of the study is to identify the effect of using swimming fins and swimming gloves on the development of 50m butterfly achievement. In addition to that he aimed at identifying the best means used for developing 50m butterfly achievement. The researcher hypothesized the existence of positive effects after using swimming fins and gloves on the development of 50m butterfly achievement. He also hypothesized significant statistical differences in the results after using these means on the development of this stroke. The researcher used the experimental method to achieve the hypothesis of the research. The subjects were (12) swimmers of the Iraqi National Swimming Federation of the ages (13 – 14) years old who swim 50m butterfly. The subjects were homogeneous in weight (54 – 59), height (1.65 – 1.62) and level of achievement. A 50m butterfly test was conducted and was considered the pretest. The subjects were divided into three equal groups; two experimental groups and one controlling group). The first group used swimming fins, the second group used the swimming gloves while the controlling group didn't use any means. The data was collected and treated statistically using t – tests, f tests and LSD test). The researcher concluded the following: - There are significant statistical differences in posttests achievement values in 50m butterfly swimming. - The greatest significant difference was found in posttests achievement values in 50m butterfly swimming in the fist group using swimming fins followed by the controlling group that did not use any of these means. - There are significant statistically differences between the first group and the second group in favor of the first group that used swimming fins for training young swimmers of the ages (13 – 14 years old) Finally the researcher recommended the following: - The coaches should pay attention to assisting means especially swimming fins during water training for butterfly stroke. Making similar researches using swimming fins on the achievement development of other types of short distance races and young age groups